A critical analysis of Bengali modern and traditional architecture using the “Deep Beauty” framework - Alam, M. M. Lekhon (Kansas State University, 2018)
The connection and relationship between nature and architecture is one which triggers the evaluation of many criticisms and questions as well as solutions. There is a new approach to design that was introduced several years ago called biophilic design, which requires contemporary designers to look at the natural processes found in nature for inspiration. In this study Bengal architecture, both vernacular and modern is described as a unique example of biomimicry and phenomenological design that could work as a solution for some other countries as well. Bengal architecture is the architecture of Wind, Water, and Clay. For this research, the focus is on the modern and traditional architecture of Bangladesh, a country with a rich cultural background. Before 1947, Bangladesh was a part of the British Empire, and in 1971, Bangladesh got independence from Pakistan in the Bangladesh Liberation War. Throughout history, Bangladesh has seen many transformations with respect to its architecture. The predominant history of Bangladesh culture has been shaped by Hinduism, Buddhism and at last by the introduction of Islam. All of these influences have shaped its cultural and traditional behavior and unfolded a different type of architectural style which is at root both native and vernacular. In Bangladesh, architecture is basic to human survival, and it is the reflection of the people’s habits, climate, culture, and tradition, and perhaps this is the only real example of Deltaic Architecture in the world. In this thesis, Bengal architecture is analyzed through Professor Gary Coates’ "Deep Beauty" framework. This report introduces Bengal architecture to the world from the very early stages to modern days through some case studies of exemplary buildings. In order to provide better architectural solutions for the future, it is essential that we look back at examples that have passed the test of time and search for the inherent qualities of traditional regional architecture. With this purpose, the report focuses on some traditional and Modern buildings: a critical analysis of the indigenous deltaic architecture of Bangladesh is presented in order to learn how it meets the criteria of Deep Beauty, for the creation of a sustainable architecture that works technologically, culturally and humanly. Three modern buildings from Bangladesh have been selected which have a profound link with the Deltaic Architecture: the National Assembly Building by American architect Louis Kahn, the Faculty of Fine Arts Building by Bangladeshi architect Muzharul Islam, and the METI Handmade School by German architects Anna Heringer and Eike Roswag. All the case studies have been critically analyzed through “Kelbaugh’s five points of a Critical Regionalism” as well as the “Deep Beauty” Framework. The results from these analyses demonstrate the inherent power and the enduring relevance of regional architecture which is deeply beautiful and inherently sustainable. [Key Words: Deltaic Architecture, “Deep Beauty” framework, Critical Regionalism, Sustainability, Contextual, Modernism, The Delta]
Keywords: Critical regionalism